How Does Empowering Leadership Influence Deep Learning? A Case Study on Teacher Performance in Elementary Schools - Ade Syarifudin; Sururi Sururi; Deni Kadarsah; Anggy Giri Prawiyogi (Journal of General Education and Humanities, 2026)
Deep learning is a new learning approach that enables students to develop higher-order thinking skills. This study aims to examine the role of principals’ empowering leadership in enhancing teacher performance in the implementation of deep learning in primary education. The study offers novelty through the integration of empowering leadership, deep learning pedagogy, and collaborative school culture in explaining improvements in teacher performance. Using a qualitative case study design at SD Labschool UPI Purwakarta, this research involved one principal, two teachers, and four students. Data were collected over two months through interviews, classroom observations, and Likert-scale questionnaires measuring teachers’ and students’ perceptions of deep learning implementation, and were analyzed using an interactive thematic approach involving data condensation, data display, and conclusion drawing. The findings reveal that principals’ empowering leadership is manifested through three main practices: building professional trust, encouraging participative decision-making, and facilitating continuous professional learning and instructional innovation. These practices strengthen teachers’ capacity to implement deep learning effectively through reflective practice, pedagogical autonomy, and meaningful student engagement. In addition, a collaborative and reflective school culture emerged as an important enabling factor that mediates and reinforces the influence of empowering leadership on teacher performance. This study highlights that empowering leadership functions not only as a managerial practice but also as a transformative force in building collective professional capacity and sustaining instructional quality improvement in primary education.